Flowchart of personal injury claims (PIC) in loss of earning / Najihan Awang @ Ali ... [et al.] - Awang @ Ali, Najihan; Nik Mustapa, Nik Ruslawati; Mat Saleh, Nurul Husna Jamian Syadatul Syaeda; Yahya, Muhammad Azri (UiTM Cawangan Perlis, 2018)
Road accidents are a major contribution in personal injury claims. The accident victims are allowed to claim a certain amount of damages from negligible parties. In Malaysia, courts adopt the traditional method of Multiplier-Multiplicand Approach to calculate the compensation amount. However, there is still no available tool to estimate personal injury claim with respect to loss of earning. This study aims to develop a flowchart for Personal Injury Claims (PIC) to calculate the compensation amount for loss of earning in Malaysia regarding the Ogden Table introduced by the United Kingdom. A flowchart is proposed and built using Microsoft Visio. The users will fill up the details displayed to get the estimated compensation amount. It is expected that claimants, courts and lawyers would be among the target users. To get started, nine elements as inputs will fill up by users. Then, there is three important processes involved in order to calculate the damages for loss of earning. In a conclusion, at the end of the session, the users will know their entitled amount of claim in loss of earning.